2021
DOI: 10.7759/cureus.20361
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Procedures in the Cervical Spine

Abstract: Cervical pain is a common symptom among the general population. When conservative strategies fail to provide pain relief, cervical spine injections may be considered. Compared with cervical surgery, cervical injections have low major complications and, with the right indication, have demonstrated good results. Traditionally, these types of procedures have been performed under fluoroscopy; however, in recent years, ultrasound has become a more common imaging modality to guide spinal injections. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…However, there are empirical data contradicting this hypothesis; the present study and several previous studies reported that the clinical results of US-guided extraforaminal injection were comparable to those of intraforaminal injection. [10][11][12]15,[17][18][19] This findings can be interpreted to mean that the range of medicine diffusion is closely related to the liquid volume.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, there are empirical data contradicting this hypothesis; the present study and several previous studies reported that the clinical results of US-guided extraforaminal injection were comparable to those of intraforaminal injection. [10][11][12]15,[17][18][19] This findings can be interpreted to mean that the range of medicine diffusion is closely related to the liquid volume.…”
Section: Discussionmentioning
confidence: 86%
“…[10][11][12] US guidance enables highresolution images of soft tissue structures (e.g., muscles, vessels, and ligaments), bony surfaces, and needle manipulation and is particularly suitable for guiding needle injection procedures in the cervical spine, where a multitude of vulnerable vessels and neural tissue structures are concentrated in a small area and around the projected needle trajectory. 12 With the emergence of US-guided SCNI studies in recent years, it is important to determine which form of SCNI guidance (CT or US) is better for CRP. Therefore, the aim of this study was to compare the clinical effects and safety of US-guided SCNI and CT-guided SCNI for CRP patients.…”
mentioning
confidence: 99%
“…On the contrary, the ability of the US is radiation-free for both patients and personnel who perform the procedure while providing detailed anatomic visualisation of soft tissues, nerves and vascular structures to potentially improve puncture precision and safety with high-resolution images in real-time [ 30 ]. Therefore, US is particularly beneficial for the management of pain in the cervical spine where a multitude of vulnerable vessels, peripheral nerves and vital soft tissues are confined to a small area [ 31 ]. Samer N Narouze et al.…”
Section: Discussionmentioning
confidence: 99%
“…US, as an alternative method for performing CILESI, could help reduce the risk of injury by allowing direct visualization of the location of the needle tip during the procedure with cross-sectional imaging. However, a technique for US-guided CILESI has not been reported, and no case series have described its safety because US has some limitations in neuraxial (epidural or intrathecal) procedures as it has a limited resolution at deep levels and near bony surfaces that affect image quality, and it is not possible to visualize the real-time propagation of the injectable in the epidural or intrathecal space [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Riveros-Perez et al introduced color Doppler imaging to confirm the correct position of the epidural needle in the lumbar spine [ 23 ]. However, this method has not been applied to CEDI [ 17 ]. For cervical epidural injection, Zhang et al reported transforaminal epidural steroid injections using sonography [ 24 ].…”
Section: Discussionmentioning
confidence: 99%